2007
DOI: 10.1093/geronb/62.3.p149
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of Older Adults' Retrieval Reluctance Through Task Instructions and Monetary Incentives

Abstract: Previous research using a noun-pair lookup task indicates that older adults delay strategy shift from visual scanning to memory retrieval despite adequate learning, and that this "retrieval reluctance" is related to subjective choice factors. Age differences in spontaneous response criteria, with older adults valuing accuracy and young adults valuing speed, might account for this phenomenon. The present experiment manipulates instructions and reward contingencies to test the flexibility of response criteria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 34 publications
11
76
3
Order By: Relevance
“…An interesting question for future research is whether participants would also respond less carefully in a perceptual task when the payoff is defined probabilistically. In sum, these results seem consistent with past research showing that increased monetary incentives motivate people to make decision more carefully in the preferential choice situations (Smith & Walker, 1993) as well as in cases where an objective criterion for choice accuracy is present (Touron, Swaim & Hertzog, 2007).…”
Section: Our Findings In Theoretical Perspectivesupporting
confidence: 91%
“…An interesting question for future research is whether participants would also respond less carefully in a perceptual task when the payoff is defined probabilistically. In sum, these results seem consistent with past research showing that increased monetary incentives motivate people to make decision more carefully in the preferential choice situations (Smith & Walker, 1993) as well as in cases where an objective criterion for choice accuracy is present (Touron, Swaim & Hertzog, 2007).…”
Section: Our Findings In Theoretical Perspectivesupporting
confidence: 91%
“…In contrast to older adults' relatively rapid shift to memory-based automaticity in reading (i.e., by Trial 6 during practice and then maintained into transfer), older adults showed minimal evidence for memory-based automaticity in alphabet arithmetic, aligning with prior research involving nonreading tasks (Hoyer et al, 2003;Jenkins & Hoyer, 2000;Rogers et al, 2000;Touron & Hertzog, 2004a, 2004bTouron et al, 2004Touron et al, , 2007. Of course, the reading task used here differed from the alphabet arithmetic task (and other tasks used in prior automaticity research) in various aspects of the task and materials.…”
Section: Discussionsupporting
confidence: 75%
“…Results from a few existing studies suggest that participants may have at least partial control over the involvement of retrieval during skill acquisition (Bourne, Raymond, & Healy, 2010;Touron & Hertzog, 2004Touron et al, 2007). For example, Bourne et al (2010) had participants repeatedly practice classifying letter strings based on whether a target letter within the string was a vowel or a consonant.…”
Section: Evidence For Control Of Retrievalmentioning
confidence: 99%
“…Finally, Touron et al (2007) used the noun-pair lookup task with older and younger adults but also included an instructional manipulation to influence learners' performance goals. Participants in the speed group were instructed that responding quickly was their primary goal and that they should use retrieval to accomplish the goal, whereas instructions for participants in the control group emphasized speed and accuracy equally.…”
Section: Evidence For Control Of Retrievalmentioning
confidence: 99%
See 1 more Smart Citation